Segregation‐controlled densification and grain growth in rare earth‐doped Y2O3. Issue 10 (24th May 2021) - Kindelmann, Moritz; Ran, Ke; Rheinheimer, Wolfgang; Morita, Koji; Mayer, Joachim; Bram, Martin; Guillon, Olivier
Abstract: Cation doping of Y2 O3 is an established approach for tailoring densification and grain growth during sintering. However, the segregation of doped cations to the grain boundary and their impact on processing are still not completely understood. Segregation can be driven by electrostatic effects due to charge mismatch with the host lattice or elastic effects induced by ion size mismatch. While segregation is caused by thermodynamics, it impacts diffusion and the kinetics of grain boundaries during densification and microstructure evolution. In this study, we utilize two isovalent dopants (La 3+ and Gd 3+ ), that is we focus on the elastic component of segregation. We investigate the densification as well as the grain growth kinetics of both doped and undoped Y2 O3 during field‐assisted sintering/spark plasma sintering (FAST/SPS). While Gd 3+ is showing no significant effect on densification, La 3+ resulted in a strongly reduced sintering activity. Furthermore, the analysis of the grain growth behavior during sintering and on predensified samples revealed a decrease in the grain growth coefficient, with La 3+ having the strongest impact. The structure and chemistry at the grain boundary were observed by aberration‐corrected TEM. While no structural change was caused by doping, the chemical analysis showed a strong segregation of La 3+ to the grain boundary, which could not be observed for Gd 3+ . The results indicate that segregated La 3+ causes a drastic decrease in grain boundary migration rates through solute drag as well as much slower sintering kinetics, likely caused by a decrease in the grain boundary self‐diffusion due to segregation. This study further underlines the importance of the elastic contribution to cation segregation and establishes a clear relationship to grain growth and sintering kinetics, which are both decreased by segregation. Abstract : Relationship between sintering and grain growth behavior of rare earth doped Y2 O3 and the structural and chemical structure at the grain boundary. The segregation of oversized La 3+ cations to the grain boundary leads to solute drag effecting densification and grain growth. ​